ANALISIS PELAPORAN KEUANGAN AGRESIF DAN AGRESIVITAS PELAPORAN PAJAK - GADIS CORNELIA AGATHA (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to analyze the relationship between aggressive financial reporting and tax reporting aggressiveness. Aggressive financial reports or earnings management is measured by discretionary accrual, while tax reporting aggressiveness is measured by discretionary permanent differences. This study uses a purposive sampling method which 18 companies listed in the Indonesia Stock Exchange (IDX) during 2010-2015 are selected as samples. The result of this study shows that there is a positive relationship between aggressive financial reporting and tax reporting aggressiveness and vice versa. This evidence implicates that companies do not make a book-tax trade off in managing commercial and taxable income.Keywords   :   aggressive   financial   reporting,   tax   reporting  aggressiveness,   earnings management, tax evasion, discretionary accrual, discretionary permanent difference